Red Cell Distribution Width sebagai Prediktor Penyakit Kardiovaskular - Bagus Fitriadi Kurnia Putra; Ugroseno Yudho Bintoro (PT. Kalbe Farma Tbk., 2020)
Baru-baru ini, sejumlah besar penelitian telah menemukan hubungan independen di luar faktor risiko tradisional antara peningkatan RDW (anisocytosis) dan penyakit kardiovaskular. Red cell Distribution Width (RDW) adalah ukuran variasi ukuran dan indeks heterogenitas eritrosit. RDW juga dikaitkan dengan mortalitas penyakit kardiovaskular dan mortalitas umum pada populasi yang berbeda. Masih harus diteliti lebih lanjut, apakah RDW hanya suatu biomarker atau juga mediator patogen untuk penyakit kardiovaskular tertentu.Recently, a large number of studies have found an independent association beyond traditional risk factors between increased RDW (anisocytosis) and Cardiovascular Diseases (CVDs). Increased RDW has been associated with different CVDs such as coronary heart disease, stroke, heart failure, atrial fibrillation, peripheral artery disease, pulmonary arterial hypertension, and venous thromboembolism, also with overall and cardiovascular mortality in different populations. It remains to be determined whether RDW is only a biomarker or also a pathogenic mediator for certain CVDs.